2019
DOI: 10.1371/journal.pntd.0006983
|View full text |Cite
|
Sign up to set email alerts
|

TIM-1 serves as a receptor for Ebola virus in vivo, enhancing viremia and pathogenesis

Abstract: Background T cell immunoglobulin mucin domain-1 (TIM-1) is a phosphatidylserine (PS) receptor, mediating filovirus entry into cells through interactions with PS on virions. TIM-1 expression has been implicated in Ebola virus (EBOV) pathogenesis; however, it remains unclear whether this is due to TIM-1 serving as a filovirus receptor in vivo or, as others have suggested, TIM-1 induces a cytokine storm elicited by T cell/virion interactions. Here, we use a BSL2 model virus that expresses EBOV glycop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 75 publications
(107 reference statements)
0
50
0
Order By: Relevance
“…In these studies, we also extensively utilized a BSL‐2 model virus of EBOV, recombinant vesicular stomatitis virus encoding EBOV glycoprotein and GFP in place of the native G glycoprotein (rVSV/EBOV GP). Our laboratory has previously found that rVSV/EBOV GP recapitulates many aspects of EBOV infection both in vitro and in vivo, including virus tropism and responsiveness to proinflammatory and anti‐inflammatory cytokines during Mϕ infection 40‐42 . Use of this chimeric virus allowed us to perform studies in a more cost‐effective manner, while maintaining the tropism of EBOV GP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In these studies, we also extensively utilized a BSL‐2 model virus of EBOV, recombinant vesicular stomatitis virus encoding EBOV glycoprotein and GFP in place of the native G glycoprotein (rVSV/EBOV GP). Our laboratory has previously found that rVSV/EBOV GP recapitulates many aspects of EBOV infection both in vitro and in vivo, including virus tropism and responsiveness to proinflammatory and anti‐inflammatory cytokines during Mϕ infection 40‐42 . Use of this chimeric virus allowed us to perform studies in a more cost‐effective manner, while maintaining the tropism of EBOV GP.…”
Section: Resultsmentioning
confidence: 99%
“…Our laboratory has previously found that rVSV/EBOV GP recapitulates many aspects of EBOV infection both in vitro and in vivo, including virus tropism and responsiveness to proinflammatory and anti-inflammatory cytokines during M infection. [40][41][42] Use of this chimeric virus allowed us to perform studies in a more cost-effective manner, while maintaining the tropism of EBOV GP.…”
Section: A Bsl-2 Model Virus Of Ebov Rvsv/ebov Gp Recapitulates Finmentioning
confidence: 99%
“…The overexpression of TIM-1 in restricted cell lines significantly enhances EBOV infection, while, in contrast, TIM-1-silenced cells markedly decrease the viral infection of even highly permissive cells [ 221 , 222 ]. In keeping with in vitro results, in vivo experiments with TIM-1-sufficient or -deficient BALB/c mice showed that TIM-1 increases viral load and the associated mortality [ 223 ]. These results imply that TIM-1 is essential for, at least, viral entry and pathogenesis.…”
Section: Interplay Of Virus Proteins and Host Factorsmentioning
confidence: 73%
“…Although previous paradigms suggest that all viral GPs orchestrate enveloped viral attachment to host cells in a lock-and-key-like manner, evidence now suggests that less-specific mechanisms of virion attachment can be utilized to facilitate internalization. Attachment factors such as lectins and PS receptors effectively bind and internalize viral particles without specific GP interaction (12,20,21,23,24). In order to interact with cellular PS receptors, viral particles must contain PS in the outer leaflet of their envelopes.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have confirmed the importance of PS receptor-mediated EBOV entry in cultured cells (17,18,(20)(21)(22)(23). Futhermore, groups examining EBOV pathogenesis in TIM -/mice found TIM1 to be critical for viral loads in the liver, kidneys, spleen, and lymph nodes, and serum cytokine induction, which are both characteristic of human EBOV infection (24,25).…”
mentioning
confidence: 95%